PENGARUH ESG RATINGS, LEVERAGE, DAN LIKUIDITAS TERHADAP KINERJA KEUANGAN DAN KINERJA PASAR (Studi Empiris pada Perusahaan Non-Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2023) - Rahmah Nuzuliani Nirmala; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2025)
This study aims to examine the role of ESG Ratings, leverage, and liquidity on financial performance and market performance of non-financial companies and listed on the Indonesia Stock Exchange during the 2021–2023 period. This research is based on stakeholder theory. The population in this study consists of non-financial companies listed on the Indonesia Stock Exchange (IDX) during the years 2021–2023. The sampling technique used is purposive sampling, resulting in 59 research samples over three consecutive years (2021–2023). The analysis results indicate that ESG Ratings and liquidity has a positive effect on financial performance. Leverage has a negative effect on financial performance. The other variables show no significant effect.